Auto-granulation of Fine Cohesive Powder by Mechanical Vibration. (2015) - Ku, Nicholas; Hare, Colin; Ghadiri, Mojtaba; Murtagh, Martin; Oram, Pascale; Haber, Richard A.
Abstract: As the size of individual particles is reduced below several microns, the interparticle cohesive forces begin to play a major role in the bulk powder behavior. Fine powders generally exhibit poor flowability as well as an affinity to agglomerate and form clusters due to this cohesion. This clustering behavior of dry, binderless particles is known as auto-granulation and can often cause difficulties in processing and handling of powders. In this study, a titania powder is vibrated under controlled conditions to induce clustering and promote agglomerate growth. The amplitude and frequency of the mechanical vibration is varied to view the effect of the input energy on the equilibrium agglomerate size. Furthermore, the densities of the formed agglomerates are measured to investigate the role of consolidation as a mechanism of auto-granulation. Given that the size of the agglomerates formed by this auto-granulation process is affected by the balance between the cohesive energy of the particles and the disruptive energy of vibration, this work provides insight into the mechanism controlling the growth of these agglomerates to an equilibrium size.